New record of Furipterus horrens (Cuvier, 1828) (Chiroptera, Furipteridae) in eastern Brazilian Amazonia - José Claudo de Sousa Monteiro; Ana Cristina Mendes de Oliveira; Fernanda Atanaena Gonçalves de Andrade; Lorrainy Simões de Sousa; Rebeca Silva Lima; Sayron Mathias Cruz dos Reis; Clarice Alves Corrêa de Souza; Ângelo Gabriel Teixeira Costa (Check List, 2024)
The bat Furipterus horrens (Cuvier, 1828) is endemic to the Neotropics, and in Brazil, it is widespread. However, there are few records in the Amazon Region where it is known only from the states of Amazonas and Pará. Here, we report the occurrence of a colony of F. horrens in an anthropogenic environment in the Brazilian Amazon. This type of habitat has not been previously reported for this species. We also compile and update the known occurrences of F. horrens in Brazil. Our new data brings to the number of localities for this species in Brazil to 76.